Laser induced synthesis and concentration dependent thermo-optical properties of silver-gold alloy nanoparticles. (26th September 2018) - Fathima, R; Mujeeb, A
Abstract: Silver and gold nanoparticles were synthesised separately in water by laser ablation method using Nd:YAG nanosecond laser. The synthesized nano solutions, mixed in an equal proportion were again irradiated by the laser to get silver-gold alloy nanoparticles. The formation of alloy nanoparticle was confirmed using UV-Visible spectroscopy. The stability of silver, gold and alloy nano colloidal solutions was established using zeta potential analysis. The structure and size of the formed alloy nanoparticles were investigated using TEM images. Concentration dependant thermal diffusivity changes in silver, gold and silver-gold alloy nano solutions were studied using dual-beam mode matched thermal lens technique. The thermal diffusivity values of the nano fluids were found to increase with the concentration.